Pembelajaran Matematika Integrasi (Materi Bilangan Pecahan dan Pengeluaran Zakat Mal Menurut Islam) - Hurriyatul annisa; Moh. Miftakhul Ulum; Muhammad Hasan Asnawi; Nur Laili Arofah (MAXIMA : Jurnal Pendidikan Matematika, 2024)
Mathematics has a close relationship with the Al-Qur'an and Hadith. Mathematics learning can be used to form education with an Islamic character because the mathematics learning process indirectly accustoms students to character according to the teachings of the Quran and Hadith. This research seeks to examine the integration of Islamic values and mathematics in order to form a generation with Islamic character. So that students can experience mathematics as part of life, every mathematics material that will be taught must be demonstrated with certain aspects that contain an understanding of religion in life, such as visual illustrations, tracing history, presenting mathematical concepts with an Islamic content. The purpose of this writing is to show how to integrate the Quran and hadith about zakat with mathematics learning about fractions. This integration concept can be used to develope mathematics teaching on fraction concepts by referring to four stages (1) knowing, (2) understanding, (3) applying, and (4) analyzing.